Fertile Goeppertella from the Jurassic of Patagonia: mosaic evolution in the Dipteridaceae-Matoniaceae lineage - Yañez, Agustina (2023)
Background and Aims: Goeppertella has been postulated as a monophyletic group, whose precise position within the Gleichenoid families Dipteriaceae and Matoniaceae, remains poorly understood. Previously described Goeppertella specimens are based on frond fragments and its fertile morphology is represented by a few, poorly preserved specimens. We describe a new species based on the largest collection of fertile specimens known to date, and discuss the evolutionary history of the genus based on the additional reproductive characters provided by the fossils described.Methods: Plant impressions were collected in Early Jurassic sediments of Patagonia, Argentina. The specimens were described, and silicone rubber casts were developed to examine in detail vegetative and reproductive features. The new species was compared with other Goeppertella species. Finally, a backbone analysis was performed in the context of a previously published combined matrix of Dipteridaceae, using the maximum parsimony criterion. Key Results: The new species is described based on a combination of features that have not been previously reported. The vegetative morphology shows affinities with most fossil and extant Dipteriaceae, contrasting with the reproductive morphology which is more comparable with the scarce number of fossil dipteridaceous forms and it is more spread in the sister family, Matoniaceae. The backbone analysis indicates that the position of the new species vary among different positions among Dipteridaceae and Matoniaceae. Additional analyses, discriminating the signal of reproductive and vegetative character, are provided to discuss the base of this uncertainty. Conclusions: We consider Goeppertella as a member of the family Dipteridaceae since we interpret most shared features with Matoniaceae as plesiomorphic conditions for the family. In contrast, most shared features with Dipteridaceae represent apomorphies for the group. Thus, Goeppertella would represent an early diverging genus in Dipteridaceae, considering the venation characters as the most important in order to define the family.